Influence of defect density on the gas sensing properties of multi-layered graphene grown by chemical vapor deposition. (April 2021) - Ricciardella, Filiberto; Vollebregt, Sten; Tilmann, Rita; Hartwig, Oliver; Bartlam, Cian; Sarro, Pasqualina M.; Sachdev, Hermann; Duesberg, Georg S.
Abstract: Chemical vapor deposition (CVD) has been demonstrated as a highly promising technique for the production of graphene on large scale and enabling tunability of the intrinsic defects of the films during the synthesis. In this work, we report on the correlation between the density of defects (DoD) and the kinetics of interaction of multi-layered graphene (MLG) with nitrogen dioxide (NO2 ) used as a target gas. We grow MLG on a pre-patterned molybdenum (Mo) catalyst layer, tailoring the DoD while growing MLG at temperatures from 850 °C to 980 °C. Analysing the Raman spectra, we show the lowering of the DoD as well as a quality dependence of MLG as a function of the growth temperature. The chemi-resistors based on MLG grown at different temperatures unambiguously highlight that, both during the exposure and the subsequent purge phase, the more defective the MLG, the more intense the NO2 's molecules interaction with MLG. Our results significantly mark a step forward in tuning the sensing properties of MLG without the need of any post-processing of the material after synthesis.